2011
DOI: 10.1371/journal.pone.0020329
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Male Caller Identity in Koalas (Phascolarctos cinereus): Acoustic Analysis and Playback Experiments

Abstract: The ability to signal individual identity using vocal signals and distinguish between conspecifics based on vocal cues is important in several mammal species. Furthermore, it can be important for receivers to differentiate between callers in reproductive contexts. In this study, we used acoustic analyses to determine whether male koala bellows are individually distinctive and to investigate the relative importance of different acoustic features for coding individuality. We then used a habituation-discriminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 49 publications
5
68
0
Order By: Relevance
“…Whether koalas attend to size-related formant information in male bellows remains to be demonstrated. However, in a previous study we showed that male and female koalas can discriminate between the bellows of different male callers and that formant-related spectral prominences contributed disproportionately to vocal identity (Charlton et al, 2011). Consequently, it seems likely that koalas perceive formant frequency-related variation in male bellows, and attend to this information in the context of identity cueing.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Whether koalas attend to size-related formant information in male bellows remains to be demonstrated. However, in a previous study we showed that male and female koalas can discriminate between the bellows of different male callers and that formant-related spectral prominences contributed disproportionately to vocal identity (Charlton et al, 2011). Consequently, it seems likely that koalas perceive formant frequency-related variation in male bellows, and attend to this information in the context of identity cueing.…”
Section: Discussionmentioning
confidence: 75%
“…In a previous study we showed that clear spectral prominences likely to represent formants are present in male koala bellows (Charlton et al, 2011). If these pronounced frequency bands in male bellows are indeed formants, i.e.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The relatively low rate of male agonistic interactions that are observed during the breeding season is most likely to be a direct consequence of this species' predominantly arboreal and nocturnal lifestyle which makes behavioural observations difficult (Martin and Handasyde, 1999;Melzer et al, 2010;Mitchell, 1990) but could also imply that competitive interactions are often resolved through signalling (as in other mammals: Bradbury and Vehrencamp, 2011). Consistent with this notion, recent work has revealed the importance of male bellow vocalisations in this species' vocal communication system for signalling identity and deterring potential rivals (Charlton et al, 2011;Charlton et al, 2013).…”
Section: Introductionmentioning
confidence: 62%